2017
DOI: 10.1038/s41389-017-0005-7
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Cadherin 6 is activated by Epstein–Barr virus LMP1 to mediate EMT and metastasis as an interplay node of multiple pathways in nasopharyngeal carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is an epithelial malignancy, which is notorious among head-and-neck cancers with its metastatic feature. Epstein–Barr virus (EBV) infection plays a fundamental role in NPC development with the mechanism is not well understood. Here we demonstrate that EBV oncoprotein LMP1 drives EMT and metastasis of NPC by reactivating the adhesion molecule, cadherin 6 (CDH6), which normally occurs in embryogenesis with unknown role in NPC. CDH6 was found to be upregulated in LMP1-positive NPC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 50 publications
(64 reference statements)
3
56
0
Order By: Relevance
“…In the present study, EBV infection induced mesenchymal phenotypes, migration, and invasion of infected cells (Figures 6 and 7). In other EBV-associated epithelial cancers, the activation of EMT was mediated by transcriptional regulators of EMT, such as ZEB1, SNAIL, and TWIST, which was followed by the induction of mesenchymal markers and the suppression of epithelial markers through the activation of cell signaling pathways, such as NF-κB, mTOR, Syk, and PI3K/Akt pathways [43][44][45][46][47][48][49][50][51]. Activation of transcriptional regulators of EMT was followed by down-regulation of epithelial markers and up-regulation of mesenchymal markers in SCC25 EBV cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, EBV infection induced mesenchymal phenotypes, migration, and invasion of infected cells (Figures 6 and 7). In other EBV-associated epithelial cancers, the activation of EMT was mediated by transcriptional regulators of EMT, such as ZEB1, SNAIL, and TWIST, which was followed by the induction of mesenchymal markers and the suppression of epithelial markers through the activation of cell signaling pathways, such as NF-κB, mTOR, Syk, and PI3K/Akt pathways [43][44][45][46][47][48][49][50][51]. Activation of transcriptional regulators of EMT was followed by down-regulation of epithelial markers and up-regulation of mesenchymal markers in SCC25 EBV cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was therefore suggested that CDH6 may be involved in the regulation of PSMA-related prostate cancer metastasis mechanisms [35]. While Goeppert et al found that CDH6 serves as a tumor suppressor gene in cholangiocarcinoma in that its expression is signi cantly lower in cholangiocarcinoma tumor tissue and that the prognosis of cholangiocarcinoma patients with low expression of CDH6 is poor [36], Zuo et al found that it is signi cantly up-regulated in nasopharyngeal carcinoma (NPC) tumor tissue and can promote NPC metastasis by inducing EMT [37]. Gugnoni et al found that CDH6 in papillary thyroid cancers (PTC) can be used as a pro-metastatic gene and serves as a biomarker in PTC cases with high invasive ability [38].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LMP1 could also downregulate the tumor suppressor miR-204 to enhance the activity of Cdc42, which mediates cellular invasive properties such as focal complex formation, integrin localization, and MMP expression [ 46 ]. A recent study also demonstrated that through the suppression of miR-203 in an NF-κB-dependent manner, LMP1 can induce activation of cadherin 6 (CDH6) to act as the synergic node of multiple pathways to promote EMT [ 47 ]. Runt-related transcription factor 2 (RUNX2) can also be upregulated by LMP1 in similar manner, and high levels of CDH6 and RUNX2 have been identified in NPC tissues from patients with bone metastasis [ 47 ].…”
Section: Alterations Of Intracellular Cell Signaling In Ebv-infectmentioning
confidence: 99%